Implementação do modelo TPM - quebra zero em máquina produtora de fitas adesivas em uma indústria química no interior de São Paulo - Silva, Nicolas Roberto Galvão da [UNESP] (2016)
Every private company has as your's main goal obtain a higher profit and efficiency in your production, therefore is necessary eliminate the shortcomings and problems present in the process. Basing on that, many companies have adopted methods and systems to assist in the tracking of possible improvements in their production. In the maintenance industry sector is not different, there are various models that can be implemented to increase the yield and productivity of the machines. A widely system used is the Lean Manufacturing, which are applied various techniques and specifics methods to help to improve and solve recurring problems. Due to the high demand and necessity for improve the yield in a specific tapes machine, it was decided apply a improvements line derived Lean System, called by Breakdown Zero, in order to maximize the process efficiency